Blue search in Kansas river database - Sama, Haritha Reddy (Kansas State University, 2008)
Students who are Research Assistants under Dr. Craig Paukert, Division of Biology Kansas State University have problems storing/retrieving their field data directly from database. There data is generally related to fishes in Kansas River. All this data is entered in the data sheets during the research in field. They enter fish related data like tag numbers (each fish caught is given a tag and after noting the data related to the fish it is left back in the river) and other information like size of the fish, place the fish was caught (stations) and information about the shore habitats, water temperature, depth etc. They also need data to recognize the aging in a recaptured fish (fish caught with a tag). The data from these data sheets is manually entered into the database. Each student has their information on the database entered (wherein they actually have to work on a single database). There is inconsistency of data. Also the database doesn't show the concentration of the fishes or location of the fishes right away. For which they require lot of analysis on the data. The main objective of this project is to provide a solution for this problem. The solution is an interface to store data and retrieve data and show the data on Maps for easy analysis and also have centralized data. The interface is user friendly which removes the hassle from entering the data manually into the database.
Keywords: Web application; Computer Science (0984)